Sistem Pakar Untuk Mendiagnosa Tingkat Stres Pada Mahasiswa Tingkat Akhir Dengan Menggunakan Metode Case Based Reasoning (CBR) Berbasis Website - Julyadin, Muhammad Rizki; Herdiansyah, Rengga (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Health has become a necessary thing for humans, almost all fields related to health services have begun to use the use of computers for their performance, one of which is diagnosing diseases for final year students who experience stress. Currently, human needs for better medical services are needed, which means the support of instrumentation and modern medical informatics (telemedicine) is needed including methods to help analyze it so that a more optimal diagnosis is produced. The Case Based Reasoning (CBR) method is one method to build a system that works by diagnosing new cases based on old cases that have occurred and providing solutions to new cases based on old cases that have the highest similarity value. In the application of the Case Based Reasoning method here, the patient will be inputted what symptoms he is experiencing. After that, the diagnosis results will come out. The results obtained by the working mechanism of the application, it can make it easier for psychologists to diagnose stress diseases of final year students and can also minimize errors in diagnosing patients.